Does cultural background influence the dissemination and severity of the COVID-19 pandemic? - Duarte, M. (2022)
The COVID-19 pandemic has spread throughout the globe affecting countries worldwide. However, several differences have been observed in the number of daily new cases, the COVID-19 reproduction rate, and the severity of the disease in different countries. Previous studies have mostly highlighted government restriction policies to mitigate the pandemic effects as reasons for such differences. This study focuses on 101 countries and proposes that each country’s cultural background is also accountable for such differences. We considered the six Hofstede’s cultural dimensions (power distance, individualism, masculinity, uncertainty avoidance, long term orientation, and indulgence) and statistically analyzed their correlation with several COVID-19 impact metrics in comparison to several restriction policies. Our results support our claim that national culture influences both acceptance and subsequent adoption of restriction policies and the implementation by each government of those policies. We highlight that the attitudes towards and trust in political institutions, policies and governance is influenced by the cultural background, which is reflected in the pandemic numbers. As a main takeaway from this study, we conclude that data-driven models which aim at predicting the pandemic impact evolution at a global scale should also include variables that reflect the cultural background of each nation.